2016
DOI: 10.1097/ftd.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Transplantation—Proteomics and Metabolomics

Abstract: Modern multi-analyte “omics” technologies allow for the identification of molecular signatures that confer significantly more information than measurement of a single parameter as typically used in current medical diagnostics. Proteomics and metabolomics bioanalytical assays capture a large set of proteins and metabolites in body fluids, cells or tissues and, complementing genomics, assess the phenome. Proteomics and metabolomics contribute to the development of novel predictive clinical biomarkers in transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 63 publications
4
13
0
Order By: Relevance
“…Currently, there is a growing body of literature demonstrating that kidney tubule health can be measured noninvasively to provide insight into kidney graft function and disease progression beyond that provided by glomerular status [10]. Clinical chemistry and biochemistry diagnostics in transplantation relies on a limited set of biomarkers and a single molecular marker will likely never be identified that captures the function of a transplant organ in all its complexity [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a growing body of literature demonstrating that kidney tubule health can be measured noninvasively to provide insight into kidney graft function and disease progression beyond that provided by glomerular status [10]. Clinical chemistry and biochemistry diagnostics in transplantation relies on a limited set of biomarkers and a single molecular marker will likely never be identified that captures the function of a transplant organ in all its complexity [5].…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive biomarkers are necessary to monitor allograft status and to predict long-term outcomes. Several candidates have been suggested as useful biomarkers for acute rejection or fibrosis of kidney allografts [56].…”
Section: Introductionmentioning
confidence: 99%
“… 8 Recent studies using multi-omics techniques have identified unique molecular signatures that confer significantly more information than the microscopy and staining measures currently used for medical diagnostics. [9] , [10] , [11] , [12] , [13] , [14] , [15] Such advanced technology paired with extensive patient databases has allowed for the discovery of a diverse set of biomarkers, shifting the focus away from a single marker to a combination of various biomarkers. Because of the complexity of the aetiology of post-transplant liver injury, prognostic and diagnostic tests will likely need to integrate multiple layers of biological information ( e.g ., transcriptomics, epigenetics, proteomics) in order to be both sensitive and specific (especially in the presence of coexisting conditions).…”
Section: Multi-omics Approach To Identifying Biomarker Signaturesmentioning
confidence: 99%
“…Less common markers may include proteomic and metabolomic biomarkers, which are explored using multi-analyte technologies that assess the complete set of proteins or metabolites of a biological sample. 9 However, findings from proteomic and metabolomic biomarker discovery studies have not been readily transferred to clinical trials due to their high complexity, relative novelty, and the intricate analytical techniques required to interpret such data. 17 , 18 Therefore, this review will focus on the biomarkers that have been described using an important number of clinical samples and that are thus more likely to be transferred to the clinical setting promptly.…”
Section: Multi-omics Approach To Identifying Biomarker Signaturesmentioning
confidence: 99%
“…Instead of the classical approach in which a candidate gene or protein guides all analyses, protein profiling provides a powerful method to analyze the role of proteins in disease processes in an unbiased manner. Proteomics assays capture a large set of proteins, providing an approach to identify possible biomarkers and mediators and the advantage of elucidating the overall patterns of lesion-induced changes at the protein level (7). Moreover, functional proteomics provides a superior capacity over other techniques to identify modified proteins involved in multiple networks of living cells or body fluids (8).…”
Section: Introductionmentioning
confidence: 99%